Movile telephony in students of physical education dependency or addiction - Daniel Álvarez-Ferrándiz (Journal of Human Sport and Exercise, 2021)
In this initial study on the dependency or addiction to mobile telephony in the university students of the Faculty of Educational Sciences of the University of Granada, two fundamental objectives are intended. First, establish the technical adequacy (reliability and validity) of the instrument and second, determine the degree of addiction / dependence to the mobile device that presents the sample object of investigation at a merely descriptive level. We have used a descriptive methodology per survey, responding to a sample of 60 subjects. Some of the conclusions of the work are: With regard to validity, we can affirm that the instrument claims to measure the construct for which it has been developed through the adaptation of other instruments, that is, it is creditor of content validity. It has also revealed the presence of a remarkable concurrent criterial validity that shows that the items individually measure the same as the scale in its entirety. In the second block of conclusions we highlight the fact that, in a general way, levels of dependency / addiction to the mobile device have been moderately low.